2007
DOI: 10.1007/s11249-007-9261-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Friction Properties of Monolayer Lubricant Films Induced by Development of Molecules’ Bonding

Abstract: Functional perfluoropolyether (PFPE) films consisting of mobile and bonded molecules are widely used for lubrication of magnetic disks. In order to clarify the influence of film composition (mobile/bonded) on tribological performance, we measured the friction properties of two types of 2 nm-thick PFPE films (functional Zdol2000 and nonfunctional Z03) under lightly loaded (loading force: 0-1 mN) and quasi-static (low rotational speed: 2.1 mm/s) conditions as a function of elapsed time. The friction force of Z03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…They observed that there is a sudden transition to high friction and vibration (bridged state) at some low touchdown pressure when the ambient pressure is decreased with the magnetic recording slider initially flying over the lubricated disk surface; they also discussed the HDI phenomena at the slider contact on the disk surface. On the other hand, to measure the tribological properties, He et al developed a pin-on-disk-type micro-tribotester that can measure adhesion and friction forces. , Their tester mainly consists of a spindle motor, a friction sensor, a slider load/unload switching mechanism, an incremental loading actuator mechanism, and an optical displacement sensor. The friction force is measured on the rotating disk surface, and the pull-off force is measured on the stationary disk surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that there is a sudden transition to high friction and vibration (bridged state) at some low touchdown pressure when the ambient pressure is decreased with the magnetic recording slider initially flying over the lubricated disk surface; they also discussed the HDI phenomena at the slider contact on the disk surface. On the other hand, to measure the tribological properties, He et al developed a pin-on-disk-type micro-tribotester that can measure adhesion and friction forces. , Their tester mainly consists of a spindle motor, a friction sensor, a slider load/unload switching mechanism, an incremental loading actuator mechanism, and an optical displacement sensor. The friction force is measured on the rotating disk surface, and the pull-off force is measured on the stationary disk surface.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to measure the tribological properties, He et al developed a pin-on-disk-type micro-tribotester that can measure adhesion and friction forces. 12,13 Their tester mainly consists of a spindle motor, a friction sensor, a slider load/unload switching mechanism, an incremental loading actuator mechanism, and an optical displacement sensor. The friction force is measured on the rotating disk surface, and the pull-off force is measured on the stationary disk surface.…”
Section: Introductionmentioning
confidence: 99%
“…In the period before TFC slider technology, when the flying clearance of pico-sliders was 5 nm or more, Z-dol with a single OH polar group at both ends of the main chain was commonly used in monolayers or more, and the bonded ratio was about 40%. In order to achieve stable flying conditions with a clearance of 1-2 nm or less, research on the functions of the bonded and mobile layers of various lubricants, surface energy, adhesion and friction force characteristics in relation to lubricant thickness has been actively conducted since around 2000 [5,6,[31][32][33][34]. Lubricants such as Z-tetraol and D-4OH with two OH polar groups at each end of the main chain, and ZTetraol MultiDentate (ZTMD) with multiple OH groups in the middle of the main chain have been developed to improve the bonding function of lubricants [35,36].…”
Section: Experimental and Theoretical Studies Of Meniscus Forces Betw...mentioning
confidence: 99%
“…筆者ら の動的吸着力の測定実験では, 半径が 1 および 2 mm のガラス球を用いており, また Tani らの論文 Tagawa, 2012, Tani, et al, 2013)では半径 1.82 mm のガラス球を, Zhang らの実験 (Zhang, et al, 2007) (Zhang, et al, 2011 Iteration number Penetration  [10 nm]…”
Section: 微小な粗さ面が接触したとき,空気中の水分子が表面に凝縮し接触突起周辺にナノメートルレベルのメニスカunclassified